Prevalence and risk factors for bovine brucellosis in the State of Santa Catarina, Brazil - Karina Diniz Baumgarten; Flávio Pereira Veloso; José Henrique Hildebrand Grisi-Filho; Fernando Ferreira; Marcos Amaku; Ricardo Augusto Dias; Evelise Oliveira Telles; Marcos Bryan Heinemann; Vitor Salvador Picão Gonçalves; José Soares Ferreira Neto (Semina: Ciências Agrárias, 2016)
A study was conducted to verify that the State of Santa Catarina has maintained a low prevalence of bovine brucellosis, which would allow the state to move forward with implementing strategies for disease eradication. The state was divided into five regions. In each region, a predetermined number of randomly selected properties was sampled. In each property, blood samples were collected from randomly selected cows with ages equal to or greater than 24 months. Sera from the animals were submitted to a serial testing protocol, with screening by the buffered acidified antigen test and confirmation by the 2-mercaptoethanol test. In each property, a questionnaire was used to identify the risk factors associated with the disease. In the state, the prevalence rate of infected herds was 0.912% [0.297 - 2.11] and infected animals was 1.21% [0.09 - 4.97]. Relative to the earlier study in 2002, there was no difference. The risk factors associated with the condition of a herd infected with brucellosis were as follows: herd size ? 12 cows (OR = 7.47 [2.14 - 34.34]) and the presence of flooded areas (OR = 5.68 [1.62 - 26.13]). In view of the low prevalence, it is recommended that the state proceed with the implementation of eradication strategies that are based on a surveillance system structured to detect and eliminate infected herds, and supported by an effective compensation fund for the replacement of seropositive animals. Additionally, the State should make a significant effort to educate and supervise producers to ensure the testing of breeding animals for brucellosis before introducing them into their properties.